The capital structure determinants of the Portuguese banking sector: a regional dynamics - Castro, N. R. V. F; Lopes, I. T. (Journal of International Studies, 2021)
This research focuses on evaluating how strongly common capital structure determinants have an explanatory power on the Portuguese banking financial leverage. It also assesses the impact of financial crisis on the banks’ leverage ratios, and its adjustments with capital regulatory requirements. A set of banks selected correspond to the group of financial entities that form the Portuguese Bank Association and that have continually operated as a unique entity over the period 2009-2018. A panel data analysis, based on a fixed effects approach, was used to assess the relationship between financial leverage and the set of selected explanatory variables. The results evidences that there is a significant impact of regulatory capital, the global financial crisis and the eurozone crisis on the leverage levels of the Portuguese banks. Over the period under analysis, regulatory capital, as well as the economic effects of the financial crisis, strongly impacted on the leverage ratios, affecting the capital structure of Portuguese banks. This research provides key outcomes about the impact of structural capital drivers on the Portuguese leverage ratios and the corresponding levels before and after the economic financial crisis. It confirms that a bank may be undercapitalized even when it holds capital above regulatory requirements.